Cerebrospinal Fluid Culture Positivity and Clinical Outcomes After Amphotericin-Based Induction Therapy for Cryptococcal Meningitis. (28th December 2015) - Rolfes, Melissa A.; Rhein, Joshua; Schutz, Charlotte; Taseera, Kabanda; Nabeta, Henry W.; Huppler Hullsiek, Kathy; Akampuira, Andrew; Rajasingham, Radha; Musubire, Abdu; Williams, Darlisha A.; Thienemann, Friedrich; Bohjanen, Paul R.; et al.
Abstract: Background.  Amphotericin-based combination antifungal therapy reduces mortality from human immunodeficiency virus (HIV)-associated cryptococcal meningitis. However, 40%–50% of individuals have positive cerebrospinal fluid (CSF) fungal cultures at completion of 2 weeks of amphotericin induction therapy. Residual CSF culture positivity has historically been associated with poor clinical outcomes. We investigated whether persistent CSF fungemia was associated with detrimental clinical outcomes in a contemporary African cohort. Methods.  Human immunodeficiency virus-infected individuals with cryptococcal meningitis in Uganda and South Africa received amphotericin (0.7–1.0 mg/kg per day) plus fluconazole (800 mg/day) for 2 weeks, followed by "enhanced consolidation" therapy with fluconazole 800 mg/day for at least 3 weeks or until cultures were sterile, and then 400 mg/day for 8 weeks. Participants were randomized to receive antiretroviral therapy (ART) either 1–2 or 5 weeks after diagnosis and observed for 6 months. Survivors were classified as having sterile or nonsterile CSF based on 2-week CSF cultures. Mortality, immune reconstitution inflammatory syndrome (IRIS), and culture-positive relapse were compared in those with sterile or nonsterile CSF using Cox regression. Results.  Of 132 participants surviving 2 weeks, 57% had sterile CSF at 2 weeks, 23 died within 5 weeks, and 40 died within 6 months. Culture positivity was not significantly associated with mortality (adjusted 6-month hazard ratio, 1.2; 95% confidence interval, 0.6–2.3; P = .28). Incidence of IRIS or relapse was also not significantly related to culture positivity. Conclusions.  Among patients, all treated with enhanced consolidation antifungal therapy and ART, residual cryptococcal culture positivity was not found to be associated with poor clinical outcomes.